Oral-resident natural Th17 cells and γδ T cells control opportunistic Candida albicans infections - Conti, Heather R. (The Rockefeller University Press, 2014)
Oropharyngeal candidiasis (OPC) is an opportunistic fungal infection caused by Candida albicans. OPC is frequent in HIV/AIDS, implicating adaptive immunity. Mice are naive to Candida, yet IL-17 is induced within 24 h of infection, and susceptibility is strongly dependent on IL-17R signaling. We sought to identify the source of IL-17 during the early innate response to candidiasis. We show that innate responses to Candida require an intact TCR, as SCID, IL-7Rα(−/−), and Rag1(−/−) mice were susceptible to OPC, and blockade of TCR signaling by cyclosporine induced susceptibility. Using fate-tracking IL-17 reporter mice, we found that IL-17 is produced within 1–2 d by tongue-resident populations of γδ T cells and CD3(+)CD4(+)CD44(hi)TCRβ(+)CCR6(+) natural Th17 (nTh17) cells, but not by TCR-deficient innate lymphoid cells (ILCs) or NK cells. These cells function redundantly, as TCR-β(−/−) and TCR-δ(−/−) mice were both resistant to OPC. Whereas γδ T cells were previously shown to produce IL-17 during dermal candidiasis and are known to mediate host defense at mucosal surfaces, nTh17 cells are poorly understood. The oral nTh17 population expanded rapidly after OPC, exhibited high TCR-β clonal diversity, and was absent in Rag1(−/−), IL-7Rα(−/−), and germ-free mice. These findings indicate that nTh17 and γδ T cells, but not ILCs, are key mucosal sentinels that control oral pathogens.